Identification of drought-responsive miRNAs and physiological characterization of tea plant (Camellia sinensis L.) under drought stress - Guo, Yuqiong (BMC Plant Biol, 2017)
BACKGROUND: Drought stress is one of the major natural challenges in the main tea-producing regions of China. The tea plant (Camellia sinensis) is a traditional beverage plant whose growth status directly affects tea quality. Recent studies have revealed that microRNAs (miRNAs) play key functions in plant growth and development. Although some miRNAs have been identified in C. sinensis, little is known about their roles in the drought stress response of tea plants. RESULTS: Physiological characterization of Camellia sinensis ‘Tieguanyin’ under drought stress showed that the malondialdehyde concentration and electrical conductivity of leaves of drought-stressed plants increased when the chlorophyll concentration decreased under severe drought stress. We sequenced four small-RNA (sRNA) libraries constructed from leaves of plants subjected to four different treatments, normal water supply (CK); mild drought stress (T1); moderate drought stress (T2) and severe drought stress (T3). A total of 299 known mature miRNA sequences and 46 novel miRNAs were identified. Gene Ontology enrichment analysis revealed that most of the differentially expressed-miRNA target genes were related to regulation of transcription. Kyoto Encyclopedia of Genes and Genomes analysis revealed that the most highly enriched pathways under drought stress were D-alanine metabolism, sulfur metabolism, and mineral absorption pathways. Real-time quantitative PCR (qPCR) was used to validate the expression patterns of 21 miRNAs (2 up-regulated and 19 down-regulated under drought stress). The observed co-regulation of the miR166 family and their targets ATHB-14-like and ATHB-15-like indicate the presence of negative feedback regulation in miRNA pathways. CONCLUSIONS: Analyses of drought-responsive miRNAs in tea plants showed that most of differentially expressed-miRNA target genes were related to regulation of transcription. The results of study revealed that the expressions of phase-specific miRNAs vary with morphological, physiological, and biochemical changes. These findings will be useful for research on drought resistance and provide insights into the mechanisms of drought adaptation and resistance in C. sinensis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12870-017-1172-6) contains supplementary material, which is available to authorized users.